2013
DOI: 10.1039/c3cc42340a
|View full text |Cite
|
Sign up to set email alerts
|

Highly enhanced thermal stability of Zn4Sb3 nanocomposites

Abstract: The effects of nano-sized TiO2 and ZnO ceramic inclusions on the high temperature stability of Zn4Sb3 have been studied using multi-temperature synchrotron powder X-ray diffraction. Samples with 9 nm TiO2 nanoinclusions exhibit remarkable stability after three heating cycles to 625 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 26 publications
4
36
0
Order By: Relevance
“…The TiO2 nanocomposite sample showed significant improvement in thermal stability by retaining 98.8 wt% of the original phase after heating to 625 K, compared with 42 wt% degradation in the pure sample [26] . Although remarkable results have been obtained both respect to the TE performance and the thermal stability at high temperatures, there is virtually no report on the practical use of Zn4Sb3 in TEGs, and the reason for this is still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The TiO2 nanocomposite sample showed significant improvement in thermal stability by retaining 98.8 wt% of the original phase after heating to 625 K, compared with 42 wt% degradation in the pure sample [26] . Although remarkable results have been obtained both respect to the TE performance and the thermal stability at high temperatures, there is virtually no report on the practical use of Zn4Sb3 in TEGs, and the reason for this is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that these doped samples are more stable than the non-doped sample under thermal cycling and during heat treatment. With the purpose of blocking the Zn diffusion inside Zn4Sb3, nano-sized ZnO and TiO2 ceramic inclusions have also been investigated [26] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations